Cosmetic wastewater primary treatment by fenton process and final polishing adsorption - Pereira, Lisiée Manzoli Gonçalves; Ferreira, Maria Eugênia de Oliveira; Brito, Núbia Natália de; Ostroski, Indianara Conceição (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
This work aimed to integrate two wastewater treatment technologies, Fenton process as the primary treatment and adsorption aiming achieve maximum removal efficiency and adequation to the environmental and water legislations. Wastewater from a cosmetics industry plant in the metropolitan area of Goiânia (Brazil) was the object of this research. It was analysed environmental parameters as absorbance, total iron, chemical oxygen demand, pH, total phenols, conductivity, H2O2, dissolved oxygen, turbidity, and total solids. They were analyzed in between processes at all stages. The effects of Fe2+ (18.42-257.89 mg L-1) and H2O2 (500-2300 mg L-1) concentrations and pH values (3.00-5.50) were studied for the Fenton process treatment. In adsorption, the activated carbon was characterized by infrared spectroscopy, elemental analysis, adsorption and desorption of N2 and thermogravimetry (TG/DTA). The effect of the contact time (4min-24h) and of the temperature variation in the system 20-60 °C were studied. By integrating the two technologies, a satisfactory removal rate was achieved for the analyzed parameters in the total time of treatment of 82 minutes